Hypoperfusion cerebral infarction after carotid artery stenting: A case report - Ma, Yuerong; Zhang, Renwei; Liu, Yumin (Frontiers in Surgery, 2023)
Carotid artery stent implantation (CAS) plays an important role in preventing cerebral infarction associated with carotid stenosis. The postoperative complications of CAS include cerebral hyperperfusion syndrome (CHS), cerebral infarction, vascular injury, carotid sinus reaction and stent restenosis. Hyperperfusion syndrome (CHS) is a serious complication after carotid endarterectomy (CEA) or CAS, which is characterized by high blood pressure, headache, epilepsy and focal neurological deficit. Therefore, it is very important to evaluate and diagnose CHS. The cerebral infarction after CAS is often caused by distal embolism due to the shedding of microemboli. With the application of distal brain protection devices, the risk of distal embolism is significantly reduced. Our case reported a rare hypoperfusion cerebral infarction after carotid artery stenting in a patient with severe carotid stenosis complicated with contralateral common carotid artery occlusion.